Investigating the Influence of Emotional Intelligence and Organizational Commitment on Organizational Citizenship Behavior: An Examination of the Workforce at PT XYZ - Situmorang, Soraya Agustina (Bina Nusantara University, 2024)
The research investigates the influence of emotional intelligence (EI) and organizational commitment (OC) on organizational citizenship behavior (OCB) within PT XYZ. OCB, which involves voluntary actions benefiting the organization, is increasingly recognized as essential for organizational success. Emotional intelligence, the ability to perceive and manage emotions, plays a crucial role in fostering these behaviors, while organizational commitment reflects the dedication and attachment employees feel towards their company. Using a cross-sectional design, data were collected from 100 employees via a structured questionnaire. Multiple linear regression analysis revealed that emotional intelligence and organizational commitment significantly and positively influence OCB. Specifically, employees with higher emotional intelligence and more substantial organizational commitment demonstrate greater engagement in discretionary behaviors that support organizational functioning. The study concludes that fostering emotional intelligence and organizational commitment within the workforce can significantly enhance OCB, contributing to improved organizational effectiveness. These findings suggest that organizations should prioritize emotional intelligence training and strengthen employee commitment to boost overall performance.